Counter-Terrorist Financing: A Good Policy Going too Far? - Michael Brzoska (Deutsches Institut für Wirtschaftsforschung (DIW), 2011)
'The money trail' of terrorist activity has become a focus of counterterrorist policy. There has been major success in implementing international standards to prevent and detect terrorist financing. Available evidence suggests that these efforts have contributed to a decrease in transnational terrorist activity. In the wake, they are likely to have contributed to a shift from transnational to "home grown" terrorism. Partly because of this change, and partly because of the continuous expansion of counter-terroristfinancing costs have begun to outweigh the costs of additional measures.
info:eu-repo/grantAgreement/EC/FP7/218105
Keywords: 330